Great Soul : Mahatma Gandhi And His Struggle With India - Lelyveld, Joseph (India : Harpercollins, 2011)
A highly original, stirring book on Mahatma Gandhi that deepens our sense of his achievements and disappointments. This is a vital, brilliant reconsideration of Gandhi s extraordinary struggles on two continents, of his fierce but, finally, unfulfilled hopes, and of his ever-evolving legacy, which more than six decades after his death still ensures his place as India s social conscience and not just India s.
Keywords: Biography -- Mahatma Gandhi